TPQ Teachers' Strategies in Developing a Culture of Islamic Religious Education Literacy at TPQ Caha Tana'o, Tonda Village - Ibnu Abbas; Ruslan Ruslan; Nasaruddin Nasaruddin (Jurnal Ilmiah Mandala Education (JIME), 2026)
This study examines the strategies implemented by teachers at the Caha Tana'o Al-Qur'an Education Park (TPQ) in Tonda Village in developing a culture of Islamic religious education literacy and its impact on students. Using a descriptive approach that involved interviews with teachers and 10 students, as well as observation and documentation, several innovative strategies were identified, including project-based learning, group discussions, the use of digital media, and routine Quran reading activities. These strategies have been proven to increase students' reading interest from 60% to 80%, their understanding of religion by up to 90%, and their student learning independence. The methodology used is a qualitative approach, with data analysis through reduction, presentation, and conclusion, in accordance with the Miles and Huberman method, with purposive subjects in a rural location with a population of approximately 1,500 people. The main findings indicate that contextual strategies that integrate local Islamic values have the potential to provide positive impacts, despite being faced with challenges such as a lack of resources (60% of TPQ lack books), low reading interest (30%), and limited internet access. Comparisons with other TPQs, such as Al-Falah, demonstrate the potential for community adaptation. The study recommends teacher training, parent-community collaboration, and resource provision to ensure the sustainability of holistic religious literacy at TPQs.